ERNESTO GEISEL E A IMPRENSA DO BRASIL: A propaganda ideológica sobre o quarto Presidente do Regime Militar brasileiro (1964-1985), entre sua eleição e posse - Barel, Moisés Stefano (2007)
At the beginning of 1970 s Brazil had a period of great economic growth and also of broad dissemination of Government actions through the existing means of communications until them to try to legitimate the Military Regime. The Country was ruled by a President who was a general Emílio Garrastazu Médici, whose administration was very well-know as the rigid years . In the middle of 1973 he decided that his successor in comand of the Republic would be a general Ernesto Geisel. The aim of this work is just to investigate the campaign of ideological propaganda performed by magazines like Manchete and Veja and by newspapers like O Estado de S. Paulo and Folha de S. Paulo to present to their readers the new President. At first, this work started through bibliographical surveys to let them know about that historic period and most of all, the documental analysis. Afterwards a study was accomplished with regard to the selected issues on magazines and newspapers above mentioned in order to find out evidences of ideological propaganda components which were performed to discover whether they acted or not as diffusers of official interests.